ANALYSIS OF STUDENTS UNDERSTANDING TOWARD ONLINE LEARNING BY USING GOOGLE CLASSROOM DURING THE PANDEMIC COVID-19 AT SMA PELITA NGABANG CLASS X IPS IN ACADEMIC YEAR 2021/2022, LANDAK REGENCY - Rita, Rita; Tuminah, Tuminah; Selong, Yustina (English Language Education Study Program, 2022)
This study aims to determine students' understanding toward online learning usingGoogle Classroomduring the PandemicCovid-19at SMA Pelita Ngabang. Beside that, the researchers conducted this research to find out the obstacles that students face during online learningusingGoogle Classroom. This research is a qualitative descriptive which conducted in tenth grade students of SMA Pelita Ngabang. Data collection techniques used were closed questionnaire, interview, and documentation related to the sources related to this research. The results of the questionnaire and the results of interview with students can be concluded that currently there were many students of tenth grade students at SMA Pelita Ngabang understand how to useGoogle Classroomalthough there were some students who did not understand how to useGoogle Classroomduring the pandemicCovid-19.The process of online learning by using mediaGoogle Classroomwas very appropriate to be applied during the pandemicCovid-19. Nevertheless, there were some obstacles that students often face when participating in the online learning processbecause of limited facilities such asAndroid phones. In addition, they often change their email passwords that could make them difficult to login because they forgot their email passwords. Regarding the network that was not good during the online learning processusingGoogle Classroom wasalso became an obstacle in the teaching and learning process.